No causal association between plasma cystatin C and cardiovascular diseases: Mendelian randomization analyses in UK biobank - Tu, Jingjing; Xu, Ying; Guo, Xu; Zhang, Jiayu; Xu, Duo; Han, Liyuan; Wang, Yue; Zhang, Boya; Sun, Hongpeng (Frontiers in Medicine, 2023)
Background: We aimed to determine whether the plasma cystatin C is a causal risk factor for cardiovascular events, stroke, myocardial infarction (MI), and cardiovascular disease (CVD) mortality by conducting Mendelian randomization (MR) designs.Methods: Our study included 277,057 individuals free of CVDs or cancer at baseline in the UK Biobank. The genetic scores of plasma cystatin C comprising 67 single-nucleotide polymorphisms were calculated on the basis of data from a large genome-wide association study. By stratifying the genetic score, we conducted cox regression to assess the relationship between plasma cystatin C and CVDs. In this study, linear MR analysis was used to estimate the causal association between plasma cystatin C and CVDs.Results: Observational analyses showed that plasma cystatin C concentrations were associated with the risk of CVDs [hazard ratios (HR) per standard deviation (SD) 1.09, 95% confidence interval (CI);1.07-1.10] and CVD mortality (1.14, 1.11-1.17). Among CVDs, plasma cystatin C were associated with stroke (1.10, 1.08-1.11) and MI (1.08, 1.07-1.10). Linear MR analysis did not provide evidence of a causal association between plasma cystatin C and the risk of CVDs [odds ratio (OR) per SD 0.96, 95% CI ;0.90-1.03], stroke (0.96, 0.93-1.01), MI (0.97, 0.91-1.03), and CVD mortality (0.98, 0.96-1.01), with consistent estimates from sensitivity analyses. Conclusion: Observational findings indicated that higher plasma cystatin C is associated with a higher risk of CVDs; According to MR studies, there is no causal association between plasma cystatin C and the risk of CVDs and CVD mortality.